2008
DOI: 10.1158/1078-0432.ccr-08-0888
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Protracted Daily Temozolomide for Low-Grade Gliomas in Adults

Abstract: Purpose: Resistance to temozolomide chemotherapy is partly mediated by O 6 -methylguanine-DNA methlytransferase (MGMT). Protracted treatment with temozolomide potentially overcomes MGMT resistance and improves outcome. We conducted a phase II study of protracted daily temozolomide in adults with low-grade gliomas. Experimental Design: Patients with newly diagnosed oligodendroglioma or oligoastrocytoma with a MIB-1index of >5% or recurrent low-grade gliomas received temozolomide (75 mg/m 2 /day in 11-week cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
101
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(110 citation statements)
references
References 38 publications
5
101
0
4
Order By: Relevance
“…29 40 high levels of MGMT are thought to contribute to resistance to TMZ. 41 Levin et al. 34 reported that TMZ was active in patients with progressive oligodendrogliomas, and that the response to treatment was associated with 1p deletion and low MGMT protein expression.…”
Section: Extracranial Skeletal Metastasis In Anaplastic Oligodendroglmentioning
confidence: 99%
“…29 40 high levels of MGMT are thought to contribute to resistance to TMZ. 41 Levin et al. 34 reported that TMZ was active in patients with progressive oligodendrogliomas, and that the response to treatment was associated with 1p deletion and low MGMT protein expression.…”
Section: Extracranial Skeletal Metastasis In Anaplastic Oligodendroglmentioning
confidence: 99%
“…In glioblastomas, MGMT methylation status in addition as a marker of prolonged survival is a predictor to therapy response (Hegi et al, 2005). In oligodendroglial tumors there is a strong association between MGMT promoter methylation and 1p19q codeletion the latter also contributing to the improved survival of patients with MGMT methylation (Levin et al, 2006;Kesari et al, 2009). MGMT alone is useful as a prognostic marker but not useful to predict outcome of adjuvant treatment in oligodendrogliomas (van den Bent et al, 2009).…”
Section: Molecular Biologymentioning
confidence: 99%
“…Kesari and colleagues conducted a phase II study of protracted daily TMZ (75 mg/m 2 /d for 49 consecutive days of each cycle, followed by 28 days off between cycles, until evidence of progression or unacceptable toxicity for a maximum of six cycles) in 44 patients with newly diagnosed low-grade glioma. After a median follow-up of 39.4 months, 21 patients progressed with an overall median progression-free survival of 38 months (Kesari et al, 2009). Patients with methylated MGMT promoter had a significantly longer overall survival (100% alive at analysis, versus 29 months with unmethylated promoter), as did patients with single or co-deleted 1p or 19q.…”
Section: Ras/mapk Pathwaymentioning
confidence: 99%